Analysis of Patent Troll Schemes and Their Arrangements in Indonesia - Adisena, Arya Hidayat; Busro, Achmad; Priyono, Ery Agus (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
The purpose of this paper is to discuss patent trolls, analyse Indonesia's regulation of patent trolls, and raise awareness of patent trolls. This research uses normative legal research methods. Normative research is conducted by examining literature data. The data is analysed using qualitative methods and presented descriptively. The conclusions drawn from this research are (1) the main problem in enforcing the law against patent trolls is the difficulty in identifying the perpetrators, who cannot be recognised solely through their identity; (2) the changes to the definition of patent enforcement in Law 6/2023 complicate this identification more than the previous rules.